2015
DOI: 10.1016/j.vetimm.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Innate and adaptive immunity against Porcine Reproductive and Respiratory Syndrome Virus

Abstract: Many highly effective vaccines have been produced against viruses whose virulent infection elicits strong and durable protective immunity. In these cases, characterization of immune effector mechanisms and identification of protective epitopes/immunogens has been informative for the development of successful vaccine programs. Diseases in which the immune system does not rapidly clear the acute infection and/or convalescent immunity does not provide highly effective protection against secondary challenge pose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
156
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 165 publications
(222 reference statements)
1
156
1
1
Order By: Relevance
“…The development of neutralising antibodies (NA) and/or of a cell-mediated immunity (CMI) have been related with the clearance of PRRSV infection or pre-exposure protection [23, 5963]. Nevertheless, since viraemia can be resolved without the development of neutralising antibodies or strong CMI, the correlates of protection are still not well understood [6468]. In addition, the genetic/antigenic diversity of PRRSV and the idiosyncrasy of each individual are also known to play a role.…”
Section: Factors Influencing Prrsv Transmissionmentioning
confidence: 99%
“…The development of neutralising antibodies (NA) and/or of a cell-mediated immunity (CMI) have been related with the clearance of PRRSV infection or pre-exposure protection [23, 5963]. Nevertheless, since viraemia can be resolved without the development of neutralising antibodies or strong CMI, the correlates of protection are still not well understood [6468]. In addition, the genetic/antigenic diversity of PRRSV and the idiosyncrasy of each individual are also known to play a role.…”
Section: Factors Influencing Prrsv Transmissionmentioning
confidence: 99%
“…PRRSV infection in pigs typically induces an impaired immune response in the host including a weak innate immunity (Albina et al, 1998), a delayed neutralizing antibody response (Loemba et al, 1996;Yoon et al, 1994), and a gradual slow development of cell-mediated immune (CMI) responses (Loving et al, 2015;Meier et al, 2003). The same scenario also applies to the PRRSV modified live-attenuated vaccine (MLV)-induced immunity (Meier et al, Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/yviro 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently observed that PRRSV-specific IFNγ-secreting cells were not detected in pigs until 2 À 3 weeks either post-infection or post-vaccination, and their frequency in peripheral blood increased slowly afterwards and remained at low levels (Loving et al, 2015;Meier et al, 2003). It is also reported that PRRSV infection reduced the surface expression of Swine Leukocyte Antigen class I (SLA-I) in macrophages and dendritic cells (Park et al, 2008;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we detected IL-15 mRNA level in PBMC at 7, 10, and 14 days after PRRSV-infected pigs (data not shown), finding that IL-15 was slightly up-regulated (about 2 fold) at 7 days after PRRSV-infected pigs, but IL-15 was suppressed at 10 and 14 days after PRRSV-infected pigs. The downexpression of IL-15 might have an effect on the suppressed NK cell cytotoxicity and the delayed low virus-specific CD8 þ T-cell response (Ferrari et al, 2013;Loving et al, 2015). In addition, IL-15 is not the only cytokine to regulate the antiviral function of NK cells and CD8 þ T cell immune response, and IFNα/β, IL-12 and other cytokines also coordinately participate in the regulation of NK cell function and CD8 þ T cell activities during viral infections (Ivashkiv and Donlin, 2014;Nguyen et al, 2002).…”
Section: Il-15 Deficient Mice Infected With Vaccinia Virus Cannot Conmentioning
confidence: 99%